Disclosures on Environmental Sustainability Issues based on Regulation and GRI - Alfonsa Roselina Purnomo; Arthik Davianti (AIBPM Publisher, 2022)
Sustainability reports are a medium forcompanies to expose their seriousness inaddressing environmental issues.Companies, especially those listed on theIndonesia Stock Exchange, are requiredby OJK through POJK 51 to present asustainability report. This study analyzedenergy sector companies listed on theStock Exchange as a sample. As a result,there were nine companies included in theanalysis. This study implemented contentanalysis. Eight main keywords will be usedto analyze the sustainability report. Theresearch compared the extent of thesustainability report under POJK 51 andthe adequacy of its scope based on theGRI series 300. The data was limited toreports from 2020 since theimplementation of POJK 51 was startedeffectively as of January 1, 2020. Theresults showed that all the analyzedcompanies had prepared the sustainabilityreport, but the report's contents were notentirely followed POJK 51 and GRI series300.